PEMBAHARUAN HUKUM KELUARGA ISLAM DI TUNISIA - Anis Hidayatul Imtihanah (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2017)
The central theme of the reform of Islamic law by Abdullah Ahmad an-Na'im is based more on the need to balance the rights of Muslims and non-Muslims and uphold the principle of equality, without gender discrimination, as well as in accordance with the concept of universalism contained in Islamic teachings that basically showing a great concern to the major elements of humanity (al-Insaniyyah). In addition to the reality of the Nation State in interconnected world, So, he focused his thinking on the implications of modern Syari'ah application to constitutionalism, justice in criminal justice, international law and human rights. Tunisia with the Family Law (Code of Personal Status/Majallat al-Ahwal al-Syakhshiyyah), explicitly prohibits polygamy, and punishes people who violate the polygamy rule with one-year imprisonment or pay a fine. Besides polygamy, the Law of Tunisian Islamic Family also stipulate that divorce could only be falling and be legitimate if done in court. Abdullah Ahmad an-Na'im is one of many prominent figures and Islamic intellectuals who had come up with various new ideas and thinking related to the re-actualization of Islamic law. The concept of modern syari'ah said that when the historical syari'ah is confronted with modern public law, it will be found that modern public law is more humanist and universal as well as closely related to human rights enforcement efforts.